Fungi Endofit dari Tanaman Secang (Caesalpinia sappan L) Sebagai Penghasil Senyawa Antioksidan: Endophytic Fungi from Secang (Caesalpinia sappan L) as Producer of Antioxidant Compounds - Amirullah, Amirullah; Sartini, Sartini; Nainu, Firzan (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
Endophytic fungi are microbes that reside symbiotically in the plant tissues with undetected negative impacts to their host plants. These fungi are able to produce elements similar to those produced by their host plants. Secang (Caesalpinia sappan L.) has been known as one of the medicinal plants that contains compounds with antioxidant activity thus promote a hypothesis that its endophytic fungi may yield a similar antioxidant effect. In this study, the isolation of endophytic fungi from Secang as the producer of antioxidant compounds was carried out. At the initial stage, endophytic fungi were isolated from the leaves, the twigs, the stems, and the rootsof Secang using the agar plate method. Pure fungi isolates were then subjected to fermentation process using the PDBgrowth medium supplemented with yeast extractand wereconstantly shaken for 12 days at a speed of 200 rpm to produce secondary metabolites. Fermentatesobtained from all fungi isolates were then extracted using ethyl acetate and further tested for their antioxidant activities. In this study, of 19 isolates that were obtained from four parts of the Secang, five fungi isolates, coded as IFD1, IFD4, IFR5, IFA1, and IFA2 were found to yield antioxidant activities demonstrated by the presence of yellow spots on the chromatogram. elementary schools representatives â€œnot good rankingâ€, the education did not influence their knowledge with a p value of 0.149. Analysis of the Wilcoxon test in all elementary schools showed a p value p â‰¤ 0,001, which meant that education had an influence on the knowledge of fifth grade students in elementary schools in Palu City.